THE MARGINALIZATION OF WOMAN LEADER IN MALANG CITY - Haboddin, Muhtar (KYBERNAN: Jurnal Ilmiah Ilmu Pemerintahan, 2024)
The article aims to explain the marginalization of women in leadership in Malang City. It turns out that the marginalization of women has been going on for a long time. Since 1942 until now women have never succeeded in becoming political leaders. This means that the political structure in Malang City is very male. The domination of men over women is a sign that political reform through direct elections does not have a positive impact on women's position in politics. The position of women is still weak and powerless against men in the mayoral election. Therefore, it is necessary to do two things simultaneously, namely encouraging political participation and developing social awareness for women so that they continue to struggle and compete for political leadership. The struggle to seize political leadership is an important agenda in building substantive democracy in Malang City.